MAC layer challenges and proposed protocols for vehicular ad-hoc networks - Gillani, S.A. (Springer Verlag, 2015)
Vehicular ad-hoc network (VANET) is a special form of mobile ad-hoc network (MANET) in which vehicles communicate with each other by creating an ad-hoc network. Before the deployment of VANET, it is necessary to address some important issues of VANET, specially concerning about architecture, routing, mobility, and security. Medium access control (MAC) protocols specify the way in which nodes share the underlying channel. As no standard exists for VANET, the research community has previously used IEEE 802.11a and 802.11b as the MAC layer access technologies. In this paper, we have discussed that the main challenge for VANET safety applications is to design an efficient MAC, so that all safety-related messages can be sent on time and such a protocol should be reliable because human lives are involved in the case of VANET. First, the challenges and requirements of a medium access protocol for VANET are discussed and then a survey of MAC solutions available in the literature to deal with these challenges in VANET is presented. Â© Springer Science+Business Media Singapore 2015.